Pathways To Islamic Education Renewal In Aceh (A Case Study of Dayah Ma'had al Ulum Diniyyah Mesjid Raya Samalanga) - Hasan Asari; Abd. Mukti; Syadidul Kahar (Nadwa: Jurnal Pendidikan Islam, 2020)
This research examines the renewal initiative at Dayah Ma'had al Ulum Diniyyah Mesjid Raya Samalanga Islamic School. This study focuses on the renewal initiative during the leadership of Abon Abdul Aziz and Abu Hasanoel Bashri. This research is qualitative research with a historical approach. This research indicates that the Al Aziziyah Samalanga Islamic Education Foundation's modernization began during the leadership of Abon Abdul Aziz in 1958 and culminated in Abu Hasanoel Bashry in 1989. Social factors had been the most dominant factors of modernization of Islamic education in the foundation, including the birth of Islamic and public universities in Aceh, the adoption of information and communication technology (ICT), the requirement of diplomas for teachers and education personnel, and the involvement of alumni in the foundation.